2016
DOI: 10.1007/s11011-016-9903-1
|View full text |Cite
|
Sign up to set email alerts
|

Selenium attenuates apoptosis, inflammation and oxidative stress in the blood and brain of aged rats with scopolamine-induced dementia

Abstract: A potent antioxidant, selenium might modulate dementia-induced progression of brain and blood oxidative and apoptotic injuries. The present study explores whether selenium protects against experimental dementia (scopolamine, SCOP)-induced brain, and blood oxidative stress, apoptosis levels, and cytokine production in rats. Thirty-two rats were equally divided into four groups. The first group was used as an untreated control. The second group was treated with SCOP to induce dementia. The third and fourth group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 39 publications
9
45
0
Order By: Relevance
“…[33] TNF-a and IL-1b are also responsible on neuronal apoptosis and inflammation in several neurological diseases such as dementia of Alzheimer's disease and injury of spinal cord. [20,34] Results of recent reports have indicated that proinflammatory cytokines including as TNF-a and IL-1a acted significant neuroprotective role in generation and maintenance of SNI, although TNF-a [35] and IL-1a [36] treatments evoke spontaneous firing of sciatic nerve. Antiinflammatory effect of HPL through inhibition of 5-lipoxygenase [37] and cytosolic phospholipase A2 [38] was reported.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[33] TNF-a and IL-1b are also responsible on neuronal apoptosis and inflammation in several neurological diseases such as dementia of Alzheimer's disease and injury of spinal cord. [20,34] Results of recent reports have indicated that proinflammatory cytokines including as TNF-a and IL-1a acted significant neuroprotective role in generation and maintenance of SNI, although TNF-a [35] and IL-1a [36] treatments evoke spontaneous firing of sciatic nerve. Antiinflammatory effect of HPL through inhibition of 5-lipoxygenase [37] and cytosolic phospholipase A2 [38] was reported.…”
Section: Discussionmentioning
confidence: 99%
“…The brain was also taken as follows; the cortex was dissected out after the brain was split in the mid‐sagittal plane. Following removal of the cortex, brain cortex was dissected from total brain . The soleus muscle samples from right legs were also taken.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations